Pengaruh Profitabilitas dan Ukuran Perusahaan terhadap Penghindaran Pajak - Yusuf Ibrahim; Hani Werdi Apriyanti (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
The practice of tax avoidance is often used by companies to legally reduce tax obligations, which can harm the state. Companies with high profitability and large size may indicate the use of more complex effective tax planning strategies. This study aims to examine the influence of profitability and company size on tax avoidance. This research is explanatory in nature. The research sample consists of 19 manufacturing companies in the food and beverage subsector listed on the IDX for the period 2020–2023, obtained through purposive sampling. Data analysis techniques include descriptive statistics, classical assumption tests, multiple linear regression, goodness-of-fit tests (F-test and coefficient of determination), and hypothesis testing (t-test). The results show that profitability has a significant positive effect on tax avoidance, while company size has a significant negative effect on tax avoidance